Economies and diseconomies of scale in software development - Comstock, C; Jiang, Z; Davies, J (2011)
Economies and diseconomies of scale-gains and losses in productivity arising from increases in project size-are of considerable, practical importance in software engineering. However, there is no consensus as to whether, in general, economies or diseconomies exist with respect to project size; neither is there any consensus on the relationship among project size, team size, and overall productivity. Using evidence from a large database of projects, this paper derives a simple parametric model for estimating development effort in terms of size and productivity factors. The model is compared with popular estimation models-the Putnam model and COCOMO II-and a possible explanation is provided for the lack of consensus. By considering also the value of the software produced, the model provides a basis for the calculation of the optimal team size for a given task, with respect to the anticipated net benefit from the development activity. © 2011 John Wiley and Sons, Ltd.